STUDI KASUS MANAJEMEN SISTEM PEMBELAJARAN GOOGLE CLASSROOM PADA PERKULIAHAN ALAT UKUR FISIKA - Melkyanus Bili Umbu Kaleka; Yasinta Embu Ika; Maria Elfrida Deno (Pendidikan Kimia Unimus, 2020)
This study aims to describe the learning activities of students during the covid pandemic 19 using the google classroom learning media and student learning achievements in physics measurement subjects. This research is an ex post facto research. The subjects in this study were all semester II students of Physics Education Study Programs, while the object of research was learning activities, learning achievements, and online learning using the Google classroom method. Data collection techniques using questionnaires and documentation. Data analysis techniques using qualitative and quantitative descriptive analysis. The results showed that online student learning activities using google classroom media viewed from 6 indicators are in the good category. Student learning achievements based on an average value of 78 with good criteria.